Gender equality and equal opportunity mechanisms in Italy - Mršević Zorica (Temida)
As a country of Southern European mentality Italy may be taken as the nearest-to-the-Balkans model of the gender equality mechanisms and necessity of their existence. Italy also might be taken as a model of domain and methods of functioning of the gender equality mechanisms as well as their connections with the EU development funds. Besides the Italian Ministry for Rights and Equal opportunities and the National Committee, the attention was paid to the whole range of local mechanisms and legal regulations dealing with advancement of women’s employment and counteracting discrimination on the labor market. In the text are analyzed through the five chapters the Italian mechanisms/institutions for gender equality as located within the European institutional environment but also within the context of Italian recent history of struggle against gender based discrimination. It was stressed that the essence of the accumulated European institutional wisdom is in diversity of the gender equality bodies rather then in their uniformity. Although the Italian mechanisms for gender equality are part of the European institutional environment their aim is to meet the internal needs for advancement of gender equality. Besides, the mechanisms also meet the demands of the international standards comprised in the documents issued by the UN and the EU. In European countries these mechanisms are frequently established and function in the domains of the labor and employment regulations, but also are located within the human rights portfolios while somewhere are connected with the minority rights and equal opportunity implementation.